ENT 530 Case Study: Doorgift Murahlah / Nur Alya Wahida Zulkiffly ... [et al.] - Zulkiffly, Nur Alya Wahida; Razimi, Nur Shahirah Puteri; Jaafar, Nur Salsabila; Kamarudin, Nuryanti; Kamarudzaman, Siti Ayuni; Zainol, Mohamad Zakaria; Abdul Razak, Muhammad Daniel; Mohamad Zainuddin, Muhammad Faiz (2021)
Doorgiftmurahlah that sells a variety of door gift items such as cookies and popcorn toward customer that are interested in finding affordable snacks for events and special occasions. The price range of products is between RM0.90 to RM30. According to the SWOT review we performed for this business, there is a big issue as well as measures that can be implemented to eliminate any further problems.